The Ugly Animal: Aesthetics, Power, and Animal-Human Relationality - Snyder, Emily (Humanimalia, 2013)
In this paper, I consider the importance of examining negative aesthetics for thinking about animal-human relations. Specifically, I concentrate on the ugly animal and ask: how might a focus on ugliness, disgust, and abjection help us to further understand animal-human relations in both theory and practice? I draw on the pigeon and pigeon feces to consider possible contributions from Donna Haraway and Michel Serres, for addressing my question. Ultimately I abandon Haraway’s respectful relationality, as well as Serres’s parasitic relationality, to consider what a politics of disgust might offer instead for a political and ethical approach to animal-human relations that is more practically attentive to discomfort, power, and conflict.